2013
DOI: 10.12659/msm.883935
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 may play a role in coexistence of depression and cardiovascular disease: A hypothesis

Abstract: Different individuals have different degrees of neuroplasticity due to their different experiences. Neuroplasticity may play a role in individual differences among neuropsychiatric disease treatment efficacy. Since the nervous system monitors and coordinates internal organ function, neuroplasticity may be associated with other diseases. Cardiovascular disease (CVD) is associated with depression, which is a disorder of disrupted neuroplasticity. MicroRNA-132 (miR-132) has a roles in neuroplasticity and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…We also validated the reduced expression of miR-132, by RT-qPCR in these samples (Figure 3B). Since miR-132 has been widely reported to regulate neuroplasticity and neural activity (Luikart et al, 2011; Zheng et al, 2013), compromised hippocampal synaptic plasticity observed in stress and depression (Pittenger and Duman, 2008), and also in our study of socially defeated mice could be attributed to the attenuated expression of miR-132. There is no human study till date that shows our novel findings (dysregulation of Drosha and a number of miRNAs, including mir-30 family members in mouse DG in CSDS model of depression) in post mortem brain samples from depressed individuals.…”
Section: Discussionsupporting
confidence: 55%
“…We also validated the reduced expression of miR-132, by RT-qPCR in these samples (Figure 3B). Since miR-132 has been widely reported to regulate neuroplasticity and neural activity (Luikart et al, 2011; Zheng et al, 2013), compromised hippocampal synaptic plasticity observed in stress and depression (Pittenger and Duman, 2008), and also in our study of socially defeated mice could be attributed to the attenuated expression of miR-132. There is no human study till date that shows our novel findings (dysregulation of Drosha and a number of miRNAs, including mir-30 family members in mouse DG in CSDS model of depression) in post mortem brain samples from depressed individuals.…”
Section: Discussionsupporting
confidence: 55%
“…34 Masson et al 35 observed that higher circulating levels of miR-132 were independently related to higher diastolic blood pressure, ischemic etiology of heart failure, higher cholesterol, and more severe symptoms of heart failure. Although the expression of miR-132 has been identified in cardiovascular disease, 36 the underlying functions and mechanisms in DCM have not been fully studied. Our findings provided evidence that miR-132 could suppress cardiocyte apoptosis and cardiac fibrosis while boosting proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Some estimates show that by 2020 the disease will be the second-most serious illness in terms of social and economic burden, exceeded only by ischemic heart disease [ 2 , 3 ]. Moreover, there are some reports suggesting that depression may coexist with other diseases, like cardiovascular disease [ 4 ]. To make matters worse, approximately one-third of DD patients do not respond to traditional pharmacological medications such as monoamine reuptake inhibitors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%